Smartphones e subjetividades: práticas de consumo de universitários(as) - Sbrissa, Luiza Elesbão (2017)
This dissertation aimed to analyze the consumption practice of smartphones by university students in the production of subjectivities. We investigated specifically the interfaces between consumption and consumerism in the era of connections. The analysis has been illustrated with the results of the empirical research of qualitative approach. The research has been sustained for nine months in participant observation with notes in the diary field and dialogical meetings held with students living on a university campus located in the southern region of Brazil. Through a psychosocial approach, we turned to the Social Representations approach also to the Studies of Material Culture. The constructs "community", "belonging" and "sociabilities" have been used to understand not only the uses but also the meanings attributed in the relations among participants and their smartphones. In general, we observed the devices by participating in the process of re-signification of the space in which they live, which is characterized by being so collective, at "home". Smartphones, therefore, sustain and reinvent sociabilities, uniting symbolically the most important aspects in the lives of these residents, contributing to the construction of their subjectivities.